Houttuynia cordata thunb. alleviates inflammatory bowel disease by modulating intestinal microenvironment: a research review - Wang, Si; Li, Lei; Chen, Yuhan; Liu, Qian; Zhou, Shengyu; Li, Ning; Wu, Yueying; Yuan, Jiali (Frontiers in Immunology, 2023)
Inflammatory bowel disease (IBD) is a complex group of chronic intestinal diseases, the cause of which has not yet been clarified, but it is widely believed that the disorder of the intestinal microenvironment and its related functional changes are key factors in the development of the disease. Houttuynia cordata thunb. is a traditional plant with abundant resources and long history of utilization in China, which has attracted widespread attention in recent years due to its potential in the treatment of IBD. However, its development and utilization are limited owing to the aristolochic acid alkaloids contained in it. Therefore, based on the relationship between the intestinal microenvironment and IBD, this article summarizes the potential mechanisms by which the main active ingredients of Houttuynia cordata thunb., such as volatile oils, polysaccharides, and flavonoids, and related traditional Chinese medicine preparations, such as Xiezhuo Jiedu Formula, alleviate IBD by regulating the intestinal microenvironment. At the same time, combined with current reports, the medicinal and edible safety of Houttuynia cordata thunb. is explained for providing ideas for further research and development of Houttuynia chordate thunb. in IBD disease, more treatment options for IBD patients, and more insights into the therapeutic potential of plants with homology of medicine and food in intestinal diseases, and even more diseases.